2015
DOI: 10.1016/j.procir.2014.07.155
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Chemically Modified Crude Jatropha Oil as a Bio-based Metalworking Fluids for Machining Process

Abstract: a b s t r a c tSynthetic amorphous silica (SAS) like NM-200 is used in a wide variety of technological applications and consumer products. Although SAS has been widely investigated the available reproductive toxicity studies are old and do not cover all requirements of current OECD Guidelines. As part of a CEFIC-LRI project, NM-200 was tested in a two-generation reproduction toxicity study according to OECD guideline 416. Male and female rats were treated by oral gavage with NM-200 at dose levels of 0, 100, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…It has been demonstrated that JO exhibits better tribological properties than other bio-oils, for example, rapeseed oil [10] and is compatible with different sealing elastomers from fuel and lubrication systems [22,23,24]. It has also been reported that the frictional coefficients are reduced by blending JO with mineral oils for different applications, namely, hydraulic fluids [25], engine oils [14], metal working fluids [26,27], automatic transmission fluids [28], drilling muds [29], etc. Negligible changes in terms of wear have been reported by using low percentages (<20%) of JO in blends with mineral oils [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that JO exhibits better tribological properties than other bio-oils, for example, rapeseed oil [10] and is compatible with different sealing elastomers from fuel and lubrication systems [22,23,24]. It has also been reported that the frictional coefficients are reduced by blending JO with mineral oils for different applications, namely, hydraulic fluids [25], engine oils [14], metal working fluids [26,27], automatic transmission fluids [28], drilling muds [29], etc. Negligible changes in terms of wear have been reported by using low percentages (<20%) of JO in blends with mineral oils [14].…”
Section: Introductionmentioning
confidence: 99%
“…Noticeable point is that viscosity has significant influence on heat transfer and energy ratio coefficient. Talib and Rahim [67] chemically modified crude jatropha oil to trimethylopropane ester (modified jatropha oil) and proved that this modified oil be a substitute of synthetic ester in MQL. In another research, Talib and Rahim [68] added hexagonal boron nitride (hBN) in different percentages and achieved better machining performance from modified jatropha oil with 0.05%wt.…”
Section: Mql With Vegetable Oilmentioning
confidence: 99%
“…A vegetable oil such as palm oil consists of a high percentage of unsaturated fatty acid in the carbon chain. Unsaturated fatty acids contain double bonds which are easily broken with high temperature [9]. This enhances the formation of high lubrication strength film on the tool-chip or tool-workpiece interface.…”
Section: Drilling Tests Under Internal Coolant Supplymentioning
confidence: 99%